MULTIPLE CASE STUDY : PRE-ANESTHESIA ASSESSMENT IN AMBULATORY ANESTHESIA PATIENTS - yusniawati, yustina ni putu; Lewar, Emanuel Ileatan; Oktaviani Tirta, Ni Putu Sapta (Nurse and Health: Jurnal Keperawatan, 2025)
Background: Pre-anesthesia assessment is a procedure to assess the feasibility and preparation of a patient's medical condition before anesthesia. Ambulatory anesthesia is a medical service that does not require hospitalization after anesthesia. Purpose: To identify case study of pre-anesthesia assessment in ambulatory anesthesia patients Methods: This study employed descriptive qualitative with a case study approach with multiple case study design. The data were collected by using interview guide. There were 5 participants included in this study. The data were analyzed by using case analysis and cross-case analysis. Results: The finding showed that 5 participants described the pre-anesthesia assessment of ambulatory anesthesia patients, namely anamnesis including identity assessment, surgical indications, and anesthetic focus data. Physical examination includes breathing, blood, brain, bladder, bowel, and bone. Diagnostic examination analysis included laboratory and radiology, ASA physical status assessment, anesthetic considerations, and special considerations including distance and access to the hospital from the hospital, as well as the responsibility of the patient, but the history of obstructive sleep apnea and special considerations were not assessed in detail. Conclusion: The pre-anesthesia assessment of the outpatient anesthesia included participant anamnesis, physical examination, diagnostic examination, assessment of ASA physical status, and assessment of anesthesia, whereas a detailed study of obstructive sleep apnea and special considerations is not carried out.